1997
DOI: 10.1097/00000658-199710000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival After Retransplantation of the Liver

Abstract: ObjectiveThe authors determined the long-term outcome of patients undergoing hepatic retransplantation at their institution. Donor, operative, and recipient factors impacting on outcome as well as parameters of patient resource utilization were examined. Summary Background DataHepatic retransplantation provides the only available option for liver transplant recipients in whom an existing graft has failed. However, such patients are known to exhibit patient and graft survival after retransplantation that is inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
172
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(204 citation statements)
references
References 5 publications
17
172
9
Order By: Relevance
“…MELD scores have been shown in other studies to predict posttransplantation survival. 9,19,24,25,28 In our study it was not predictive of survival in HCV patients partially due to low (3 yr) survival even in the moderate MELD score range. [20][21][22][23][24][25] Given the mean MELD score Ͼ25 at the time of evaluation for reTX, it is not surprising that these patients were often not offered a retransplant or could not survive long enough to get the organ they needed.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…MELD scores have been shown in other studies to predict posttransplantation survival. 9,19,24,25,28 In our study it was not predictive of survival in HCV patients partially due to low (3 yr) survival even in the moderate MELD score range. [20][21][22][23][24][25] Given the mean MELD score Ͼ25 at the time of evaluation for reTX, it is not surprising that these patients were often not offered a retransplant or could not survive long enough to get the organ they needed.…”
Section: Discussioncontrasting
confidence: 76%
“…Those retransplanted within 1 yr of initial transplant had poorer survival (3-yr survival, 46%). Other studies have found many variables that may contribute to poorer survival including recurrent HCV, 14 ChildTurcotte-Pugh score, 25 hepatic encephalopathy, 25 intensive care stay, 14,28 poor renal function, 14,19,20,22,25,29,30 donor age, 11,14,17,20,27 prothrombin time, 11,20,25 time interval from initial transplantation, 14,27 recipient age, 14,20,22,25,27,30 ventilatory status, 6,20 bilirubin level, 6,14,19,20,22,29,30 physical condition, 31 and intraoperative blood loss. 22,30 Interestingly, many patients in this study had isolated variables or poor outcomes (51% had bilirubin Ͼ10 mg/dL and 25% had serum creatinine Ͼ 2 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retransplantation of the liver (reOLT) after failure of the first graft is considered to carry a higher risk, with higher morbidity and lower survival than for the first transplantation [l, 2,3,4,5,6,7,8,9,10,111. In consideration of the often lower survival rate after reOLT, the increasing donor shortages, the pressure of increasing numbers of retransplant candidates on the waiting lists, and the higher costs of such procedures, it is important for one to evaluate the results of reOLT in order to compare the outcome.…”
Section: Introductionmentioning
confidence: 99%